2010
DOI: 10.1002/acp.1638
|View full text |Cite
|
Sign up to set email alerts
|

Did you see the unicycling clown? Inattentional blindness while walking and talking on a cell phone

Abstract: We investigated the effects of divided attention during walking. Individuals were classified based on whether they were walking while talking on a cell phone, listening to an MP3 player, walking without any electronics or walking in a pair. In the first study, we found that cell phone users walked more slowly, changed directions more frequently, and were less likely to acknowledge other people than individuals in the other conditions. In the second study, we found that cell phone users were less likely to noti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
202
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(221 citation statements)
references
References 34 publications
(85 reference statements)
13
202
0
2
Order By: Relevance
“…Attentional deficits increase when using ear buds or cell phones at the same time as riding a bicycle [40,41]. According to Haddon [21], it seems to be easier to make environmental changes rather than to try to change human behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Attentional deficits increase when using ear buds or cell phones at the same time as riding a bicycle [40,41]. According to Haddon [21], it seems to be easier to make environmental changes rather than to try to change human behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Users are also exposed to constantly changing surfaces and other outdoor features that are difficult to replicate on the treadmill which could have an adverse impact on PWS and the user's ability to input accurately. Hyman et al [10] reported that users walked slower and were more unaware to nearby events when using mobile phones. Users could be further affected if they also had to carry bulky objects during interaction, as shown by [21,22].…”
Section: The Effects Of Mobilitymentioning
confidence: 99%
“…This cognitive distraction of mobile phone users on roads decreased situation awareness and thus increased unsafe behaviors and the risk of accidents and injuries regardless of pedestrian gender or age (Hyman, Boss, Wise, McKenzie, & Caggiano, 2010;Nasar, Hecht, & Wener, 2008;Stavrinos, Byington, & Schwebel, 2009). …”
Section: Safety Concern Increase With Increased Smartphone Usagementioning
confidence: 99%